Тектоніка геосолітонних родовищ нафти і газу - Лубков, М.В. (Геоінформатика, 2017)
З метою дослідження тектоніки геосолітонних родовищ нафти і газу на основі варіаційної скінченно- елементної методики для в’язкопружної моделі Кельвіна—Фойта змодельовано сучасні геотектонічні рухи та напружено-деформований стан в околі геосолітону. Показано, що на тектонічний розвиток структури прирозломного геосолітону найбільше впливає вертикальне підняття активного мікроблока вздовж його центрального розлому. Цей рух сприяє зростанню тиску в нафтогазових пластах і приводить до інтенсивного підняття земної поверхні в околі геосолітонного родовища, яке може бути зафіксовано геодезичними і геофізичними методами. Насувні та скидові горизонтальні рухи регіонального характеру також помітно впливають на тектонічний розвиток структури геосолітону і, відповідно, на зміну тисків у його нафтогазових пластах. Моніторинг сучасних вертикальних рухів земної поверхні в околі геосолітонного родовища дає змогу виявити і відокремити його структуру і тим самим локалізувати місця можливого накопичення вуглеводневої сировини. Виявлення зони зниженого тиску вздовж центральної вертикальної труби геосолітону пояснює механізм вертикальної міграції глибинних гарячих флюїдів, а також процеси передавання вуглеводнів у центральній трубі та їх сепарацію і накопичення в колекторах геосолітону. С целью исследования тектоники геосолитонных месторождений нефти и газа на основе вариационной конечно-элементной методики для вязкоупругой модели Кельвина-Фойгта проведено моделирование современных геотектонических движений и напряженно-деформированного состояния в окрестности геосолитона. Показано, что на тектоническое развитие структуры приразломного геосолитона наибольшее влияние оказывает вертикальное поднятие активного микроблока вдоль его центрального разлома. Это движение способствует росту давления в нефтегазовых пластах и приводит к интенсивному поднятию земной поверхности в окрестности геосолитонного месторождения, которое может быть зафиксировано геодезическими и геофизическими методами. Надвиговые и сбросовые горизонтальные движения регионального характера также заметно влияют на тектоническое развитие структуры геосолитона и, соответственно, на изменение давления в его нефтегазовых пластах. Мониторинг современных вертикальных движений земной поверхности в окрестности геосолитонного месторождения позволяет выявить и выделить его структуру и тем самым локализовать места возможного накопления углеводородного сырья. Выявление области сниженного давления вдоль центральной вертикальной трубы геосолитона объясняет механизм вертикальной миграции глубинных горячих флюидов, а также процессы передачи углеводородов в центральной трубе, их сепарацию и накопление в коллекторах геосолитона. Purpose. In our time, the efficiency of oil-gas explorations closely connected with scientific and technic software of this activity. It concerned different geologic-geophysical models of the oil-gas deposits. In forming processes, transfer and accumulation processes of hydrocarbons, mechanism of their vertical migration is very important. Among the model, where such mechanisms are considered, geosoliton conception is popular enough. The geosoliton conception is in a good agreement with lot of geologic and cosmogenic ideas. It connects principals of biogenic and abiogenic hypothesis of hydrocarbon forming, which come from mantle with hot high-pressure fluids via fault pour channels- chimneys. Another hand, under influence of hot fluids oil-gas transformation of sediment organic substance takes place. On the base of geosoliton degassing mechanisms many different types of oil-gas fields models are considered.
The central vertical fault geosoliton chimney is a main element of the energy-mass transfer process. It forms positive geostructure for pumping oil-gas component in its axing central part. The abnormal high pressure of the accumulated gases in central axing part of the geostructure leads to their penetrating to the collector layers. There system of deposits, which consist of gas caps, oil collars and source formation water, is forming. It is interesting to investigate vertical movements of the earth surface in vicinity of the geosoliton oil-gas fields under the action of modern geotectonic movements. This information can be useful to detect the geosoliton structure and respectively the possible places of the oil-gas deposits. Another hand, the practical interest presents exploration of the press-deformable state in vicinity of the geosoliton structure, because press drops between pour substance in the geosoliton chimneys and surrounded rocks regulate the processes of transfer and accumulation of hydrocarbons.
Design/methodology/approach. On the base of variation finite element method for visco-elastic environment, we carried out modeling of the geotectonic movements, which appear in vicinity of the geosoliton oil-gas fields under the action of active surrounding microblocks of crystalline fundament. In addition, we carried out modeling of the press-deformable state of the geosoliton oil-gas fields.
Findings. The results of computer modeling of the geotectonic movements in vicinity of the geosoliton oil-gas fields under the action of active surrounding microblocks of crystalline fundament show the most influence on the tectonic development of the near-fault geosoliton makes vertical raising of the active microblock along its central fault. Moreover, this movement contributes pressure increasing in the oil and gas reservoirs and leads to intensive raising of the earth surface in vicinity of geosoliton oil-gas field, which we can fix by geodesic and geophysical methods. Thrusts and discharges horizontal movements of region character also act on the geosoliton structure tectonic development and respectively on the pressure changing in its oil and gas reservoirs. Therefore, monitoring of the modern vertical movements of the earth surface in vicinity of the geosoliton oil-gas fields allows to find and distinct its structure and so to localize possible accumulation places of hydrocarbons. Discovering places of decreasing pressure along the central vertical geosoliton chimney explains the mechanism of vertical migration of hot fluids and transfer processes of hydrocarbons in the central chimney and their separation and accumulation in the geosoliton collectors.
Practical value/implications. One can use obtained results for practical geologic works with a purpose to search places of hydrocarbon stuff accumulation in vicinity of geostructures close to the geosolitons.